Enhancing web supported learning in higher education by adding a management layer to LMSs - Pinto, Carlos Sousa (2012)
There are many situations in the e-Learning experiences that can compromise the success of the courses. Many times simple reasons are great enough to motivate people to abandon them. For example, if someone does not execute a programmed activity inside the defined window of time, it can compromise the rest of the course to that person. In such situations it would be important that the teacher knew about the situation in useful time, to be able to take any corrective action. Another example could be presented, involving the professor and the learners. Let us assume that an activity A2 is programmed to be executed by the learners and that it depends on the previous knowledge of the result of the evaluation of a work submitted by the learners to the teacher (activity A1). If the teacher doesn’t inform the learners about their classification in useful time, that can compromise the execution of the activity A2. It seems to be necessary to use mechanisms of automatic management, in real time, of the envolvement of each participant in a distance learning course using LMS (Learning Management System). Such a functionality allows the detection of deviations to the scheduled activities planned for each actor. If it is the case, the referred mechanism can initiate the process of sending notifications to the relevant entities, enabling the correction of these deviations. Several organizations and consortiuns, involving the industry, governmental institutions and universities, are developing projects of standardization. It seemed important to us to see how the referred aspects were covered by those projects, and to perceive how it could be possible to articulate our work with the ones that are available from these organizations and consortiuns. This article describes the work that the authors are developing towards the specification of a layer for real-time management of user interactions with LMSs, during the operationalization of a course, and also includes a management meta-data model, related to that management layer.